1999
DOI: 10.1038/sj.gt.3301026
|View full text |Cite
|
Sign up to set email alerts
|

LPD lipopolyplex initiates a potent cytokine response and inhibits tumor growth

Abstract: Our laboratory has recently developed a lipopolyplex response required assembly of DNA into a lipoplex or the consisting of DOTAP:cholesterol liposomes, protamine LPD lipopolyplex. Except for the heart, elevated levels of sulfate, and plasmid DNA (LPD) that provides improved cytokine were observed in all organs (lung, liver, kidney systemic gene delivery compared with lipoplex following and spleen) where LPD is known to have gene transfer tail vein injection in mice. Because endothelial cells are the activity.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
104
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 192 publications
(110 citation statements)
references
References 44 publications
(39 reference statements)
6
104
0
Order By: Relevance
“…The peak times for each cytokine were similar to those in previous reports. 4,5 In GdCl 3 -pretreated mice, the amounts of these cytokines were significantly lower than those in the saline-pretreated mice. The amount of TNF-␣, IFN-␥, and IL-12 in serum at the peak times was reduced 25-fold, three-fold, and 23-fold in GdCl 3 -pretreated mice, respectively.…”
Section: Increases In the Liver And Spleen After Lipoplex Injection Amentioning
confidence: 91%
See 3 more Smart Citations
“…The peak times for each cytokine were similar to those in previous reports. 4,5 In GdCl 3 -pretreated mice, the amounts of these cytokines were significantly lower than those in the saline-pretreated mice. The amount of TNF-␣, IFN-␥, and IL-12 in serum at the peak times was reduced 25-fold, three-fold, and 23-fold in GdCl 3 -pretreated mice, respectively.…”
Section: Increases In the Liver And Spleen After Lipoplex Injection Amentioning
confidence: 91%
“…[6][7][8] It appears that such cytokines activate the immune system and induce strong antitumor effects in mice. 4,5 On the other hand, Li et al have shown that such cytokines, which are secreted after intravenous injection of lipoplexes, can be toxic and cause short-term gene expression and refractory behavior on repeated dosing at frequent intervals. 9,10 This is a potential problem in gene therapy using plasmid DNA.…”
Section: Increases In the Liver And Spleen After Lipoplex Injection Amentioning
confidence: 99%
See 2 more Smart Citations
“…However, such viral vectors can have some harmful antigenicity, and serious concerns have been raised regarding the use of viral vectors, especially in clinical trials. Nonviral carriers, such as cationic liposomes, 14,15 avoid such problems. Furthermore, nonviral vectors may be good clinical options because they may be more efficient and less labor intensive than viral vectors, although the present gene transfection efficiencies still need to be improved.…”
mentioning
confidence: 99%